Investasi sebagai Oasis Ekonomi: Perlindungan Hukumnya di Tengah Efisiensi APBN - Sandy Hukunala (Jurnal Hukum Lex Generalis, 2025)
The Indonesian government's recent fiscal efficiency policy reflects a rigorous approach to controlling national spending. In this context, both foreign and domestic investment serve as strategic and vital alternative sources of financing for national development. Analogous to an oasis amid a fiscal desert, investment plays a key role when the state's fiscal space is increasingly constrained. However, legal protection for investment still faces numerous challenges, such as weak law enforcement, overlapping regulations, and disruptions by non-state actors such as community organizations (ormas). This research aims to analyze the legal protection of investment amid the government's budget efficiency efforts. The study employs a normative juridical method with statutory, conceptual, and case-based approaches. The findings reveal that although Indonesia's investment regulations have developed normatively, their implementation remains weak, particularly in ensuring legal certainty and security for investors. This research concludes that a responsive, equitable, and sustainable legal protection model is urgently needed for investment to effectively serve its function as a development instrument in times of limited fiscal capacity.